Ag, Ge dual-gradient substitution for low-energy loss and high-efficiency kesterite solar cells. Issue 42 (22nd October 2020) - Fu, Junjie; Kou, Dongxing; Zhou, Wenhui; Zhou, Zhengji; Yuan, Shengjie; Qi, Yafang; Wu, Sixin
Abstract : A generic Ag, Ge dual gradient substitution is proposed to minimize the bulk and interface recombination losses in kesterite solar cells. Abstract : A major obstacle hindering further development of kesterite Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells is the inherent recombination losses that occur both via bulk defects and charge extraction interfaces. Herein, we propose a generic Ag, Ge dual-gradient absorber architecture, involving a downshift of absorber VBM at the front contact and an upshift of absorber CBM at the back contact, to improve device performance. We experimentally show that the substitution of Cu by Ag allows for larger band bending at the p–n junction, and the substitution of Sn by Ge imposes an additional drift field within the quasi-neutral region. Additionally, the Ag and Ge ions diffusing into the bulk absorber passivate the deleterious CuZn and CuSn deep-level defects. In turn, accelerated charge extraction, transport and minimized recombination loss offered surprising gains in V oc and J sc, and the dual-gradient device achieved a maximum efficiency of 12.26% with an improved V oc, deficit of 553 mV. This Ag, Ge graded-substitution approach offers an alternative absorber architecture to improve the V oc, deficit in future high-efficiency kesterite PV cells.